‘Restriction of access’ is displacement: a broader concept and policy - Michael M Cernea (Forced Migration Review, 2005)
Recent changes in the World Bank’s policy on resettlementhave dramatic implications for those displaced by conservation projects, for governments, NGOs andresearchers.